2016
DOI: 10.1007/s12119-016-9374-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Religious Commitment on Women’s Sexual Self-Esteem

Abstract: Religious commitment is associated with decreased sexual activity, poor sexual satisfaction, and sexual guilt, particularly among women. The purpose of this paper was to investigate how religious commitment is related to sexual self-esteem among women. Participants included 196 female undergraduate students, 87 % of whom identified as Christian. Participants completed the Sexual Self-Esteem Inventory for Women (SSEI-W), Religious Commitment Inventory-10, Revised Religious Fundamentalism Scale, Brief Sexual Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…Therefore, the decreasing trends in period and cohort RRs in the four countries are mainly associated with efforts conducted by governmental and non-governmental institutions to decrease the HIV/AIDS burden in those respective countries [ 22 , 23 , 24 , 25 ]. The most significant decrease of the period and cohort RRs in the DRC might also be explained by socio-cultural and demographic factors, which have influenced the population of DRC and their sexual behavior [ 41 , 42 , 43 ]. Although governmental and non-governmental institutions have made many efforts in decreasing the HIV/AIDS burden in the respective countries, the decrease is not yet sufficient [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the decreasing trends in period and cohort RRs in the four countries are mainly associated with efforts conducted by governmental and non-governmental institutions to decrease the HIV/AIDS burden in those respective countries [ 22 , 23 , 24 , 25 ]. The most significant decrease of the period and cohort RRs in the DRC might also be explained by socio-cultural and demographic factors, which have influenced the population of DRC and their sexual behavior [ 41 , 42 , 43 ]. Although governmental and non-governmental institutions have made many efforts in decreasing the HIV/AIDS burden in the respective countries, the decrease is not yet sufficient [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that sexual guilt continues to pervade religious, married individuals (Peterson, 1964), as some scholars have suggested that religiosity can bring a more permanent sense of anxiety, guilt, and tension surrounding sexuality (Runkel, 1998). This is perhaps due to some religious teachings condemning any sexual activity only for pleasure, rather than for procreation (Abbott, Harris, & Mollen, 2016; Cowden & Bradshaw, 2007). Therefore, research suggests that religiosity could negatively influence sexual satisfaction by imbuing the sexual relationship with sexual guilt, though the role of marital status remains a matter of inquiry for this connection.…”
Section: Sexual Guiltmentioning
confidence: 99%
“…Evidence on the association between religiosity and sexual self-esteem or sexual assertiveness is limited, even in Christian samples. One study found a negative link between religiosity and sexual self-esteem among participants raised as Catholics (Abbott, Harris, & Mollen, 2016). In another study, religiosity correlated negatively with sexual assertiveness (Curtin, Ward, Merriwether, & Caruthers, 2011).…”
Section: Associations Of Religiosity With Risky Sexual Scripts Riskymentioning
confidence: 99%